Early Cretaceous ammonites from eastern Heilongjiang, northeastern China, and their chronostratigraphical significance - Li, Gang; Bengtson, Peter (Cretaceous research, 2018)
A low-diversity ammonite fauna is described from the Qihulin Formation of the dominantly non-marine Longzhaogou Group exposed in Mishan and Hulin counties in eastern Heilongjiang, northeastern China. The fauna consists predominantly of Pseudohaploceras? cf. nipponicum Shimizu, 1931, and Pseudohaploceras? peideense (Liang, 1982), with subordinate Eogaudryceras (Eogaudryceras) cf. yunshanense (Liang, 1982). The occurrence of Pseudohaploceras? and previously reported bivalves suggest an early Aptian age for the Qihulin Formation. The early Aptian transgression advanced from the east across the Hulin and Mishan area into the Jixi Basin and resulted in the deposition of the marine beds of the Qihulin and lower Chengzihe formations. The Qihulin Formation can be correlated with the lower part of the Chengzihe Formation.
Available online 25 October 2017
Gesehen am 11.02.2020